Analysis Of Determinants That Affect Earnings Quality In Transportation, Logistics, And Trans-portation Infrastructure Operator Companies - Putri, Shafa Firzani Azzahra; Wijayanti, Anita (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research examines the key determinants affecting earnings quality in logistics and transportation companies listed on the Indonesia Stock Exchange during the 2018-2022. The study employs panel data regression analysis using EViews 12 software. The dataset comprises annual financial reports from selected companies, incorporating company size, profit growth, profitability, liquidity, and managerial and institutional ownership. The findings reveal that company size, profitability, and liquidity positively and significantly influence earnings quality. Conversely, managerial and institutional ownership do not demonstrate a statistically significant effect. Furthermore, the COVID-19 pandemic has significantly impacted earnings performance within this sector, particularly in notable shifts in profitability and liquidity. These findings underscore the critical role of financial management in sustaining and enhancing earnings quality. Consequently, companies should refine their profitability and liquidity strategies to ensure profit stability and bolster financial transparency, making them more appealing to investors and other stakeholders. This study offers a novel contribution by assessing the impact of the COVID-19 pandemic on earnings quality in the transportation and logistics sector. This area has received limited attention in prior research.